Comics In Translation Teaching - Краевска, Моника (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
This paper concentrates on comics from the point of view of translation teaching. The focus is laid on two key issues: comics as a translation task and comics as a coursebook of translation. In the first part of the text difficulties in the translation process are described that result from the specificity of the comic (i.e. a combination of the word and the drawing). In this part a variety of examples is provided, including phrasemes, word games, and onomatopoeias. In the second part of the paper, the comic book entitled In the head of the translator (Gdansk, 2019) is presented, which elaborates on the history of translation, types of translation, and the translation process.